Air-Cooling Used For Metal Cutting - Boswell, Brian; Chandratilleke, Tilak (Science publications, 2009)
Air-cooling and dry machining are both being trialled as possible solutions to the metal cutting industry’s long running problems of extending tool life, reducing tool failure and minimising the heat generation at the tool tip. To date, large amounts of expensive coolant which cause both environmental damage and health hazards have had to be used. The introduction of dry machining is the goal of today’s metal cutting industry that tirelessly endeavours to reduce machining costs and impact from chemicals in the environment. Modern tool tips are already capable of maintaining their cutting edge at higher temperatures, but even with these improvements in tool materials, the cutting edge will eventually break down. Applying cold air to the tool interface of these modern tool tips will also help prolong their tool life reducing the cost of metal cutting. Dry machining incorporating air being directed on to the tool interface is considered in this paper as a possible alternative for harmful liquid-based cooling. However, low convective heat removal rates associated with conventional air-cooling methods are generally inadequate for dissipating intense heat generation in the cutting processes, and suitable improved cooling methodologies have yet to be established.